Kalimat Penderita Afasia: Studi Kasus pada Anggela Efellin - Febriani, Rezia Delfiza; Ngusman, Ngusman; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The porpuse of this research is to describtive (1) kind and (2) type of sentence that produce by afasia. Sufferer methodology that used in this afasia sufferer teenager 16 year old named Anggela Efellin. According to research result and discussion in counclude that teen with afasia suffer of the subject (1) can produce news sentence, question sentence, order sentence, single sentence, and complex sentence, (2) can produce sentence with type S-P, P-S, S-K, P-K, S-P-K, S-K-P, K-P-S, P-S-K, S-P-O, O-P-S, K-S-P-O, and S-P-O-K.